Process Production of Fishball Using Design of Fishball Moulding Machine in The Center of Testing The Application of Fishery (BBP2HP), Jakarta. - Adam Sultoni; Sri Subekti (Journal of Marine and Coastal Science)
Meatball is round-shaped food which contains meat as the basic ingredient and it becomes an original Indonesian food. Meatball can be made or created manually by hand or meatball machine. In this the modern era, a lot of meatball sellers are using meatball machine in order to get a maximum  and desired meatball results therefore the meatball machine is needed to accelerate the production process, faster than manual process.Meatball machine can produce more meatball (1000 meatballs per day) compared with manual process which can only produce 200-400 meatballs per day.  This internship was carried out to learn the production design for fish meatball production in BBP2HP through Triple screw with horizontal model. It consists of three basic process such as preparation, installation, and trial phase. The equipments which are used in running this system are masks, welding goggles, gloves, electrode, work outfit, saw blades, hammers, grinders, electric drill, hacksaw, lathes, work shoes, and sigmat.   Meatball machine is designed with stainless steel and can easily be used. This machine has horizontal-shaped body (Length x Height x Wide = 848 x 500 x 313 mm), 200 watt electricity, 5 kilograms grinding capacity, and 120 meatballs per minute production speed. It is suitable for home scale production with low electricity to save the cost.